Opportunity Lost? Revisiting RecordTV v MediaCorp TV - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2012)
Taking the Singapore Court of Appeal’s Decision in RecordTV Pte Ltd v MediaCorp TV Singapore Pte Ltd [2011] 1 SLR 830, this article seeks to argue that the copyright fair dealing defence would have been the more appropriate basis to exempt RecordTV, a digital recording service for recording television programmes, from primary copyright liability. This judicial approach towards legalising digital video recorder (“DVR”) services is more suitable taking into consideration the following: The role and objectives of copyright law in Singapore; the history and development of the fair dealing defence (including the latest amendments pursuant to the US-Singapore Free Trade Agreement); the global trends relating to user rights and information technology through a comparative study of similar cases in other jurisdictions; and a policy assessment of Singapore’s interests in promoting innovation and development against the backdrop of proprietary copyright protection.